Some issues of legal regulation of the interpreter’s participation in civil proceedings (Journal of actual problems of jurisprudence, 2023)
Although the Civil Procedure Code of the Republic of Kazakhstan pays great attention to translators involved in civil proceedings, the solution of this issue is not enough and still requires improvement. The article states that translators who participated in civil proceedings have special responsibilities, which, when participating in civil proceedings, must have certain language qualifications and a level of knowledge in the necessary areas. At the same time, it is necessary to pay special attention to the issue of regulating the responsibility of translators in civil proceedings. The purpose of the study: to analyze the theoretical and regulatory provisions on the legal status of an interpreter involved in civil proceedings. The idea of the study: to summarize the results obtained during the study, to give the main conclusions and recommendations. Scientific significance of the work: the level of development and maturity of modern Kazakh civil procedural law, in particular, the norms governing the legal status of the translator in civil proceedings, the formation of prerequisites that guarantee the democracy of justice and the implementation of the principle of its procedural language. Practical significance: determination of the ability of the interpreter participating in the judicial process to exercise real protection of rights and freedoms through the procedural language enshrined in the Research methodology: the development of the institution of persons involved in civil proceedings is based on a logical legal analysis and comparison of the principles that define the industry. The value of the conducted research. Legal regulation of the power of translators to participate in civil litigation and filling gaps in ways to address these issues. Key words: civil procedure, participants in a civil case, plaintiff, defendant, language of legal proceedings, translator, procedural rights, procedural duties.